2020
DOI: 10.1371/journal.pone.0228859
|View full text |Cite
|
Sign up to set email alerts
|

Similar but different: Profiling secondary school students based on their perceived motivational climate and psychological need-based experiences in physical education

Abstract: The purpose of this study was to provide more insight into how the physical education (PE) context can be better tailored to the diverse motivational demands of secondary school students. Therefore, we examined how different constructs of student motivation in the context of PE combine into distinct motivational profiles, aiming to unveil motivational similarities and differences between students' PE experiences. Participants were 2,562 Dutch secondary school students, aged 12-18, from 24 different schools. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 64 publications
1
21
0
1
Order By: Relevance
“…La teoría de Metas de Logro (AGT; Ames, 1992) es otra de las teorías ampliamente desarrollada en el ámbito educativo y considera que en entornos de logro (e.g., educativo), el principal objetivo consiste en mostrar competencia. Está demostrada la relación de factores disposicionales y ambientales, como el clima motivacional creado por otras personas (e.g., profesor) (Harwood, 2016), con diferentes variables a nivel académico, como la percepción de competencia (Weeldenburg et al, 2020). Según esta teoría, dos climas motivacionales predominan en contextos sociales de situaciones de logro: clima motivacional hacia la maestría (aprendizaje) y clima motivacional hacia el rendimiento (ejecución) (Walling & Duda, 2016).…”
Section: Introductionunclassified
“…La teoría de Metas de Logro (AGT; Ames, 1992) es otra de las teorías ampliamente desarrollada en el ámbito educativo y considera que en entornos de logro (e.g., educativo), el principal objetivo consiste en mostrar competencia. Está demostrada la relación de factores disposicionales y ambientales, como el clima motivacional creado por otras personas (e.g., profesor) (Harwood, 2016), con diferentes variables a nivel académico, como la percepción de competencia (Weeldenburg et al, 2020). Según esta teoría, dos climas motivacionales predominan en contextos sociales de situaciones de logro: clima motivacional hacia la maestría (aprendizaje) y clima motivacional hacia el rendimiento (ejecución) (Walling & Duda, 2016).…”
Section: Introductionunclassified
“…Even though past literature has advanced in regard to motivational climate assessment in the PE context, it seems that most research has focused its attention on the teacher-oriented climate [ 2 , 22 , 23 ], ignoring students’ perception of motivational climates created by peers to be learning-oriented or performance-oriented. As reported by Papaioannou [ 8 , 9 ], children interpret the same environment or context differently based on their previous experiences, personality differences, or behaviors exhibited by teachers and peers.…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to analyze the associations of motivational learning- and performance-oriented climates created by teachers and peers on PE grades, considering needs satisfaction as a mediator in this relationship. Based on past literature examining the role of motivational climates and needs satisfaction, it is hypothesized that: (a) learning-oriented climates created by teachers and peers have a positive association with needs satisfaction [ 19 , 22 ]; (b) performance-oriented climates created by teachers and students have a negative relationship with needs satisfaction [ 4 ]; (c) needs satisfaction is positively and significantly related with PE grades [ 2 , 4 , 19 ]; and, (d) motivational climates could have an indirect association with PE grades through the satisfaction of needs [ 2 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various studies have shown that teaching style could affect motivation during the students' training process [1][2][3] and, in addition, as other authors state [4], decades of research confirm that one of the keys to determining the quality of the students' experience is the motivational climate created by teachers in their classes. The relationship between dispositional and environmental factors has been demonstrated, such as the motivational climate created by other people (e.g., the teacher) [5], with different academic variables: Motivation [6,7], the perception of competence and autonomy [8,9], school commitment [10], adolescent adjustment [11], academic achievement [12], or academic performance [13]. For this reason, the role of the teacher is recognized amongst these environmental factors [14], and the motivational climate that their role generates is so important that some authors emphasize that it may be responsible for the students' academic success or failure [15].…”
Section: Introductionmentioning
confidence: 99%
“…The motivational classroom climate generated by the teacher has been widely studied in different educational contexts, especially in primary [8,30] and secondary education [9,[31][32][33]. Some studies have also been carried out in the university context [34,35].…”
Section: Introductionmentioning
confidence: 99%